Phytoremediation capability of Typha latifolia L. to uptake sediment toxic elements in the largest coastal wetland of the Persian Gulf. (March 2023) - Haghnazar, Hamed; Sabbagh, Kourosh; Johannesson, Karen H.; Pourakbar, Mojtaba; Aghayani, Ehsan
Abstract: The present study evaluated the status of sediment toxicity and pollution, and the phytoremediation capability of Typha latifolia L. (TlL) within the largest coastal wetland in the southwest of Iran, the Shadegan International Wetland. In eight sampling sites, covering the entire wetland, the concentration of six toxic elements (As, Cr, Cu, Ni, Pb, and Zn) in the surface sediment, root, and stem of TlL were measured. The results indicated that mean concentrations of Cr, Cu, Pb, and Zn were found to be higher than those in the local background, which likely indicates anthropogenic sources of these elements. Due to the presence of a nearby landfill, the results of modified pollution index (MPI) and aggregate toxicity index (ATI) indicated a moderately-heavily polluted level and moderate to high toxic degree, respectively. However, the medium-low level of toxicity toward living of organisms (21 % probability) was detected based on the assessment of the Sediment Quality Guidelines (SGQ). The results of our study indicate that the root and stem tissues of TlL are capable of acting as an indicator of Cu/Pb/Zn and Zn pollution in sediment, respectively. Considering the potential of phytoremediation, TlL represented both phytostabilization and phytoextraction capabilities for Pb and Zn and a significant increase was observed in the phytoremediation capability by increasing the distance from the landfill area. According to the results of the metal accumulation index (MAI) and comprehensive bioconcentration index (CBCI), TlL grown in the study area showed an acceptable performance in the accumulation of multiple toxic elements compared to that in Turkey, India, and Poland. Overall, TlL is a good candidate for the phytoremediation of sediments contaminated by Pb and Zn. Highlights: Mean concentrations of Cr, Cu, Pb, and Zn were higher than their local background values. The landfill area is responsible for a moderately-heavily pollution level and high toxicity levels. Typha latifolia L. is capable of acting as an indicator of Cu/Pb/Zn pollution in sediment. Typha latifolia L. represented phytoremediation capability for Pb, and Zn.